QUALITY OF CARE DAN HAK-HAK KONSUMEN KELUARGA BERENCANA: REVIU ATAS HASIL-HASIL PENELITIAN* - Agus Dwiyanto (Populasi, 1997)
This piece of writing is aimed to discuss on how muchpracticeof family planning services have put attention to rights of family planning consummers. The discussion is based on researches carried out either in Indonesia or in other developing countries. In fact, the services in those countries have not given total freedom to clients of family planning to choose contraception devices appropriate to their goals and interests. The services have neither guaranteed the clients' rights to get comprehensive information about contraception nor aboutfamily planningservices. Furthermore, they have not been capable of giving secure services to their clients. From the discussion, the writer offers some issues of research necessary to examine on purpose of protecting family planning consumers' rights.